Rechtsgeschäftliche Verpflichtung und autonome Bindung: zu den Entstehungsgründen vermögensaufstockender Leistungspflichten im Bürgerlichen Recht - Lobinger, Thomas (Mohr Siebeck, 1999)
Does German civil law recognize involuntary assignment of liabilities to enrich someone besides voluntary contractual obligations? Thomas Lobinger examines this problem and provides suggestions for its solution.Contractual obligation of value-adding performance requires volition on the part of the obligator according to the traditional doctrine. Judicial decisions and scientific research today recognize such obligations also in the absence of volition. The author examines the scope of the modern concepts on the emergence of value-adding performance obligation in civil law based on the principle of volition. He gives a special treatment of insignificant mental reservations and legal implications in transactions involving mistake. He also examines the problem of the lack of conscious declaration and gives a new interpretation of §§ 170 ff. BGB dealing with agents liability and representation by estoppel.
Keywords: Hochschulschrift; Willenserklärung; Leistungspflicht; Vertrag; Deutschland